Correction: The first two examples of halogen bonding with a sigma hole-donating fluorine in the Csp3–F⋯Osp3 interaction from polyfluorinated trans-dihalo-palladium(ii) di-substituted pyridine complexes. Issue 99 (28th November 2019) - Elakkat, Vijayanath; Chang, Chu-Chun; Chen, Jun-Yu; Fang, Yung-Cheng; Shen, Chia-Rui; Liu, Ling-Kung; Lu, Norman
Abstract : Correction for 'The first two examples of halogen bonding with a sigma hole-donating fluorine in the Csp 3 –F⋯Osp 3 interaction from polyfluorinated trans -dihalo-palladium(ii ) di-substituted pyridine complexes' by Vijayanath Elakkat et al., Chem. Commun., 2019, DOI: ; 10.1039/c9cc06731k .